Interim guidance on the preparticipation physical examination for athletes during the SARS-CoV-2 pandemic - Diamond, A. B.; Narducci, D. M.; Roberts, W. O.; Bernhardt, D. T.; LaBella, C. R.; Moffatt, K. A.; Nuti, R.; Powell, A. P.; Rooks, Y. L.; Zaremski, J. L. (Current Sports Medicine Reports, 2020)
The American Medical Society for Sports Medicine (AMSSM) convened a writing group to address the current evidence and knowledge gaps regarding preparticipation evaluation of athletes during the SARS-CoV-2 pandemic. The writing group held a series of meetings beginning in April 2020. The task force reviewed the available literature and used an iterative process and expert consensus to finalize this guidance statement that is intended to provide clinicians with a clinical framework to return athletes of all levels to training and competition during the pandemic. The statement is not intended to address treatment, infection control principles, or public health issues related to SARS-CoV-2. The AMSSM task force acknowledges the clinical uncertainty, evolving public health objectives, and the limited data currently available to create this guidance statement.